Akuntabilitas Supervisi Akademik Profetik Berbasis Hadis dalam Penguatan Kompetensi Guru - Faizah, Anastasya Rahma Nur; Sahudi, Sahudi; Syafitri, Firdha Masya Aulia (Program Studi Manajemen Pendidikan Islam UIN Sunan Ampel Surabaya, 2023)
Academic supervision is frequently reduced to a formal administrative procedure, whereas its core essence is to enhance instructional quality. This qualitative single-case study aims to analyze the actualization of the leadership hadith as a foundation for prophetic accountability in academic supervision at SDN 3 Sawoo, and its implications for strengthening teacher competence within the Independent Curriculum framework. Data were gathered through interviews, observations, and documentation, then analyzed using data condensation, thematic categorization, and triangulation techniques. The findings indicate that spiritual responsibility is integrated into four operational stages: rotating scheduling, classroom observation, checklist-based recording, and evaluation via dialogic coaching. The primary constraints identified are the acting principal's limited time due to dual assignments and operational budget constraints. Theorizing from the data, this study conceptualizes a prophetic accountability cycle consisting of amanah > muraqabah > muhasabah > islah, which bridges transcendental commitment with professional performance evidence. However, the program's success remains evident only at the process level, meaning its long-term impact on teacher competence warrants further longitudinal inquiry. This study recommends incorporating spiritual values to optimize academic supervision effectiveness in elementary schools.